Liquid ceramic and preparation method thereof
Liquid ceramics with a three-dimensional porous network structure address the brittleness and high-temperature processing issues of traditional ceramics, offering high hardness and wear resistance without high-temperature calcination, facilitating easy processing and reduced environmental impact.
Patent Information
- Application Number
- CN202411543122.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
AI Technical Summary
Ceramic products are hard and brittle, difficult to process, and require high-temperature burning, which is energy-intensive and polluting.
A method to prepare liquid ceramics that form a three-dimensional porous network structure with silicon-oxygen bonds, allowing for processing and application on curved surfaces without high-temperature calcination, using silica sol, silane composite modifier, and controlled pH adjustments to ensure high hardness and wear resistance.
The liquid ceramics provide high hardness and wear resistance after solidification, enabling easy processing and application on complex surfaces while reducing energy consumption and emissions.
Smart Images

Figure CN119241073A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to liquid ceramics and a preparation method thereof. Background Art
[0002] Ceramic products have a long history. Ceramic tiles and porcelain panels sintered at high temperatures are durable, non-combustible, water-resistant, wear-resistant, weather-resistant, and beautiful. They are indispensable and commonly used products in the construction field. In particular, glazed tiles and large rock panels developed in recent years are even more popular in the market. However, they have the following two disadvantages: First, they are hard and brittle, easy to break, inconvenient to process, and easy to damage during installation; second, high-temperature burning consumes too much energy and emits polluting gases. In order to improve these disadvantages, and under the guidance of energy conservation, emission reduction and environmental protection, research and development entities have begun to develop ecological panels, including cement panels, calcium silicate panels, magnesium panels, composite panels and other inorganic panels that can be burned without high temperatures, such as Chinese patent application No. 201210138195.7, published on 2 The patent document of 012.09.19 discloses a self-cleaning, anti-fouling and hydrophobic film layer based on enamel surface and its preparation method. The hydrophobic film layer comprises, by volume percentage: 0.1-10% of a film-forming agent, 10-75% of a co-solvent, 0.5-10% of a catalyst, and 5-70% of a hydrophobic agent; its preparation method comprises: (1) mixing the weighed co-solvent and the catalyst, sealing, stirring, and then dropping the film-forming agent to obtain a mixed solution; (2) soaking the enamel substrate in the above-mentioned mixed solution, taking out the enamel substrate and keeping it warm at 50-70°C, then placing the warmed enamel substrate in a dry atmosphere to cool naturally, then placing it in a cool and dry place, and finally soaking it in a hydrophobic agent and drying it.
[0003] In existing architectural decoration, there are special designs, such as Roman columns, irregular convex bodies, etc., which require ceramic tiles to be easy to process and cut and can be laid on curved surfaces or corner surfaces. However, the above literature uses a sol-gel method to prepare SiO 2 The thin film of particles can reduce the hydrophilicity of the surface of the enamel material, increase the contact angle of the surface droplets, and make the film layer have the functions of self-cleaning, anti-fouling and hydrophobic. The film coating on the tile can only play the self-cleaning, anti-fouling and hydrophobic functions, and cannot achieve the properties of being in a fluid state at the beginning and then ensuring high hardness and high wear resistance after solidification. Summary of the invention
[0004] The object of the present invention is to provide a liquid ceramic and a preparation method thereof, which can ensure coating in a fluid state and have a high hardness after solidification, so that it can be convenient for processing and cutting after combining with other substrates and can be laid on curved surfaces or corner surfaces.
[0005] In order to achieve the above object, the present invention provides a method for preparing liquid ceramics. S1: Add 150g of silica sol, 90g of silane composite modifier and 10g of accelerator into the reactor in sequence; S2: stirring the mixed solution in step S1, so that the silica sol undergoes a polycondensation reaction to form a three-dimensional porous network structure connected by silicon-oxygen bonds, and at the same time, the silane-based composite modifier undergoes a dehydration condensation reaction with the silica sol, so that the silanol or hydroxyl groups in the silica sol react and connect to form long chains interspersed in the three-dimensional porous network structure; S3 changes the accelerator component to adjust the pH value, repeats steps S1 to S2 to conduct experiments, and determines the accelerator with the best component by observing the reaction rate in step S2 and the product after the reaction; S4 determines the quality of the dispersant through the additive test, and then determines the quality of the antifoulant through the antifoulant test; After determining 0.5 g of dispersant, 3.0 g of antifouling agent and 10 g of accelerator of the optimal component, S5 adds 10 g of accelerator of the optimal component, 90 g of silane composite modifier, 10 g of accelerator, 0.5 g of dispersant, 0.3 g of wetting agent, 3.0 g of antifouling agent and 0.1-0.3 g of isopropanol in sequence according to the weight ratio, and after sufficient reaction, it is dried to form a glaze layer.
[0006] The above setting, due to the high bond energy of the silicon-oxygen bond, is not easily destroyed by the outside world, which makes the stability, high temperature resistance and aging resistance of the three-dimensional porous network structure very good. At the same time, the long chains formed by the silanol or hydroxyl connection are interspersed in the three-dimensional porous network structure, thereby increasing the flexibility of the three-dimensional porous network structure, and making the surface continuity and smoothness of the formed glaze layer better. In this way, after the liquid ceramic is sprayed onto the ecological brick, the ecological brick combined with the liquid ceramic does not need to undergo a high-temperature calcination process, and can have high hardness and high wear resistance. The composition of the promoter is determined through the optimal component promoter test. The experiment found that the reaction is fast to form powdered precipitated silica, and the reaction is slow. After several hours of sufficient reaction, it is dried and dehydrated to form a continuous phase thin layer of glaze. Increasing the promoter component and increasing the hydrogen ion concentration will move the resin hydrolysis reaction and the silica sol condensation reaction to the right, and the positive reaction will accelerate. If the hydrogen ion concentration is too high, the reaction will be violent and explosion will occur, so it is necessary to determine the optimal composition of the promoter, and then make the promoter ensure the speed and ensure the structural stability of the glaze. In this way, the liquid ceramic at the beginning can be combined with the ecological board, and can be paved on curved surfaces or corner surfaces. After a certain period of time, it solidifies to form a high-hardness surface to meet the decorative requirements.
[0007] Furthermore, the silane-based composite modifier includes a composite modifier formed by mixing silane and a bridging resin-R group or a composite modifier formed by mixing a silane coupling agent and a bridging resin-R group.
[0008] The above arrangement facilitates the reaction between the silane-based composite modifier and the silica sol.
[0009] Furthermore, the accelerator is a mixed solution of acetic acid, citric acid and formic acid.
[0010] The above settings ensure that the pH value is stable and moderate, avoid over-rapid reaction, and allow the reaction to proceed slowly and fully.
[0011] Furthermore, the reaction formula of the polycondensation reaction of the silica sol in step S2 is as follows: ; The above arrangement facilitates the formation of a three-dimensional porous network structure mainly composed of silicon-oxygen bonds in the glaze surface. Since the bond energy of silicon-oxygen bonds is extremely high, the porous network structure is very stable and has good high temperature resistance and aging resistance.
[0012] Furthermore, the step S2 also includes a resin hydrolysis reaction, and after the hydrolysis reaction, an active functional group with R-COOH or R-OH is generated. The reaction formula for generating the R-OH active functional group is as follows: ; The active functional groups of R-COOH or R-OH undergo dehydration condensation reaction with silanol (-SiOH) or hydroxyl (-OH) in silica sol. The reaction formula is as follows: .
[0013] The above arrangement enables the silanol or hydroxyl groups in the silica sol to be connected to form long chains that are interspersed in the three-dimensional porous network structure, thereby increasing the flexibility of the three-dimensional porous network structure and the continuity and smoothness of the glaze surface.
[0014] Furthermore, the dispersant is selected through an additive test, and the test is as follows: Add different types of additives in the same volume into step S2, observe the test effects of different types of additives, screen out the best additive in the test effect, and then conduct tests again in different proportions to obtain the additive with the best proportion in the test effect, and mix the additives with the best proportion to form a dispersant for preparing liquid ceramic raw materials.
[0015] The above arrangement facilitates the selection of the most effective dispersant, thereby helping to improve the surface fluidity of the glaze layer, making the surface of the glaze layer smoother and flatter.
[0016] Further, the antifouling agent is selected through an antifouling agent test, and the test is as follows: Different types of antifouling agents are added to step S2 in the same volume, the test effects of different types of antifouling agents are observed, the best antifouling agent in the test effect is screened out, and then the test is carried out again at different proportions to obtain the best ratio range in the test effect, and further tests are carried out at different proportions in the best ratio range to screen out the antifouling agent with the best ratio, and finally the antifouling agent with the best ratio is determined as the antifouling agent for preparing liquid ceramic raw materials.
[0017] The above configuration can effectively improve the anti-fouling property by adding an optimal proportion of anti-fouling agent.
[0018] Furthermore, adding color paste to liquid ceramics can form liquid ceramics of different colors.
[0019] The above settings can meet the needs of different decorations.
[0020] The present invention also provides a liquid ceramic, which comprises the following preparation raw materials according to weight ratio: 150g of silica sol; 90g of silane composite modifier; 10g of accelerator; 0.5g of dispersant; 0.3g of wetting agent; 3.0g of antifouling agent; and 0.1-0.3g of isopropanol.
[0021] The above setting, due to the high bond energy of the silicon-oxygen bond, is not easily destroyed by the outside world, which makes the stability, high temperature resistance and aging resistance of the three-dimensional porous network structure very good. At the same time, the long chains formed by the silanol or hydroxyl connection are interspersed in the three-dimensional porous network structure, thereby increasing the flexibility of the three-dimensional porous network structure, and making the surface continuity and smoothness of the formed glaze layer better. In this way, after the liquid ceramic is sprayed onto the ecological brick, the ecological brick combined with the liquid ceramic does not need to undergo a high-temperature calcination process, and can have high hardness and high wear resistance. The composition of the promoter is determined through the optimal component promoter test. The experiment found that the reaction is fast to form powdered precipitated silica, and the reaction is slow. After several hours of sufficient reaction, it is dried and dehydrated to form a continuous phase thin layer of glaze. Increasing the promoter component and increasing the hydrogen ion concentration will move the resin hydrolysis reaction and the silica sol condensation reaction to the right, and the positive reaction will accelerate. If the hydrogen ion concentration is too high, the reaction will be violent and explosion will occur, so it is necessary to determine the optimal composition of the promoter, and then make the promoter ensure the speed and ensure the structural stability of the glaze. In this way, the liquid ceramic at the beginning can be combined with the ecological board, and can be paved on curved surfaces or corner surfaces. After a certain period of time, it solidifies to form a high-hardness surface to meet the decorative requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a flow chart of the working method of the present invention.
[0023] Figure 2 It is the effect diagram of the present invention. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] Embodiment 1.
[0026] like Figure 1 As shown, a method for preparing liquid ceramics, S1: Add 150g of silica sol, 90g of silane composite modifier and 10g of accelerator into the reactor in sequence.
[0027] S2 stirs the mixed solution in step S1 to cause the silica sol to undergo a polycondensation reaction to form a three-dimensional porous network structure connected by silicon-oxygen bonds. The reaction formula of the polycondensation reaction is as follows: ; At the same time, the resin hydrolysis reaction also occurs in the mixed solution, and the active functional group with R-COOH or R-OH is generated after the hydrolysis reaction. The reaction formula for generating the R-OH active functional group is as follows: ; After the silane composite modifier undergoes a dehydration condensation reaction with the silica sol, specifically, the active functional groups of R-COOH or R-OH undergo a dehydration condensation reaction with the silanol (-SiOH) or hydroxyl (-OH) in the silica sol. The reaction formula is as follows: ; The silanol or hydroxyl groups in the silica sol react and connect to form long chains that are interspersed in the three-dimensional porous network structure, thereby increasing the flexibility of the three-dimensional porous network structure and the continuity and smoothness of the glaze surface.
[0028] S3 changes the accelerator components to adjust the pH value. Since the accelerator is a mixed solution of acetic acid, citric acid and formic acid, in this embodiment, by changing the H + The concentration is achieved, and steps S1 to S2 are repeated to conduct experiments. The best component accelerator is determined by observing the reaction speed in step S2 and the product after the reaction; for example, different acetic acid, citric acid and other acidic solutions are selected to form several accelerators to perform steps S1 and S2, and then the curing speed and whether the product after the reaction forms a continuous phase thin layer glaze or implosion occurs are recorded. If implosion occurs, it means that the hydrogen ion concentration is too high, and the acidic solution is reduced. If the reaction is too slow, it means that the hydrogen ion concentration is too low, and the acidic solution can be increased. The accelerator component is found to be a mixed solution of acetic acid, citric acid and formic acid. The ratio of acetic acid, citric acid and formic acid is not limited. As long as the H + The concentration is sufficient to meet the pH value required for the reaction.
[0029] S4 determines the dispersant by a dispersant additive test. The test is as follows: different types of additives are added to step S2 in the same volume, the test effects of different types of additives are observed, and the three best additives in the test effects are selected. The test effects are shown in Table 1 below. Table 1
[0030] From the test results in Table 1, it can be concluded that the test effects of the three additives of 410 leveling agent, 414 composite leveling agent and 417 leveling agent are the best. Then, the 410 leveling agent, 414 composite leveling agent and 417 leveling agent are tested again at different proportions of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1.0% of the weight ratio of the silane composite modifier, respectively, to obtain the best proportion of the additives in the test effect. In this embodiment, the best proportion of 0.5% of the 410 leveling agent additive and the best proportion of 0.3% of the 414 composite leveling agent are mixed to form a dispersant in the preparation of the liquid ceramic raw material. In this embodiment, the SF337 wetting agent in Table 1 is selected as the wetting agent in the preparation of the liquid ceramic raw material; The antifouling agent is then determined by the antifouling agent test, which is as follows: Different types of antifouling agents are added to step S2 in the same volume, and the test effects of different types of antifouling agents are observed to select the best antifouling agent in the test effect. The test results are shown in Table 2 below. Table 2
[0031] From the test results in Table 2, it can be concluded that the test effect of EC-505 antifouling agent is the best. Then, the EC-505 antifouling agent is tested again at different proportions of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 10%, and 12% of the weight ratio of the silane-based composite modifier to obtain the best proportion range in the test effect. In this embodiment, the best proportion range is 3%~5%. In the best proportion range, the test is further carried out at different proportions of 3%, 3.5%, 4%, 4.5%, and 5% of the weight ratio of the silane-based composite modifier to screen out the antifouling agent with the best proportion. In this embodiment, the best proportion of the antifouling agent is 3%. Finally, it is determined that the best proportion of 3% antifouling agent is the antifouling agent for preparing liquid ceramic raw materials.
[0032] S5 After determining the dispersant, wetting agent, antifouling agent and accelerator of optimal concentration, add the accelerator of optimal concentration, silane composite modifier, accelerator, dispersant, wetting agent, antifouling agent and isopropyl alcohol in sequence according to the weight ratio. After sufficient reaction, dry it to form a glaze layer. In this embodiment, the glaze layer is set to be transparent.
[0033] In one embodiment, if liquid ceramics of different colors need to be prepared, color paste can be added on the basis of the liquid ceramic raw materials. For example, to prepare white liquid ceramics, white paste ground to less than 25 microns is added on the basis of the liquid ceramic raw materials, and a white glaze layer can be obtained after sufficient reaction and drying.
[0034] In the specific application of liquid ceramics, the ecological bricks are firstly made into flat white bottom bricks after surface sanding and alkali-proof treatment. The ecological bricks include calcium silicate boards, magnesium boards, cement boards and honey aluminum metal boards, etc. Then, the liquid ceramics fully reacted in step S5 are sprayed on the ecological bricks. After the liquid ceramics are solidified, an enamel-like glaze layer can be formed on the ecological bricks. The various physical and chemical properties of the glaze layer are shown in Table 3 below. Table 3
[0035] like Figure 2 This is the effect of observing the glaze surface under a microscope.
[0036] Embodiment 2.
[0037] The present invention provides a liquid ceramic, which is prepared by the preparation method of embodiment 1. The liquid ceramic includes the following preparation raw materials in weight ratio: Silica sol 150g; Silane composite modifier 90g; Accelerator 10g; Dispersant 0.5 g; Wetting agent 0.3g; Antifouling agent 3.0 g; Isopropyl alcohol 0.1~0.3g; The silane-based composite modifier includes a composite modifier formed by mixing silane and a bridging resin-R group or a composite modifier formed by mixing a silane coupling agent and a bridging resin-R group, and the accelerator is a mixed solution of acetic acid, citric acid and formic acid.
[0038] In this embodiment, 0.2 g of isopropyl alcohol is used according to a weight ratio, and the silane-based composite modifier is a composite modifier formed by mixing silane and a bridging resin-R group.
[0039] In another embodiment, the raw materials for preparing the white pulp according to the weight ratio are as follows: 30g of all-red titanium dioxide; 10g superfine talcum powder; 15g ultrafine barite powder; White carbon black 2g; Isopropyl alcohol 41.5 g; Dispersant 1.5g.
[0040] The following two examples demonstrate that the liquid ceramic prepared by the present invention can save costs.
[0041] Example three.
[0042] The inorganic sheet-3D printing-liquid ceramic process is used to prepare decorative panels, which has good economic benefits and can be industrialized. The pilot-scale small-scale production is used as a calculation example: The average market price is used as a reference, and the cost part is shown in Table 4: Table 4 Product cost
[0043] The cost of the surface decoration layer is as follows: 1. Primer UV dosage: 30g / ㎡, 60 yuan / kg, i.e. 2 yuan / ㎡.
[0044] 2. Intelligent 3D printing: accuracy 720*1440dpi, 4-nozzle speed (material 2.5m*1.25m), standard accuracy (4pass, whole board) 45㎡ / h; higher accuracy (6pass, whole board) 30㎡ / h, ultra-high accuracy (8pass, whole board) 22㎡ / h; the test adopts higher accuracy calculation.
[0045] The cost is moderate, at 21 yuan / ㎡.
[0046] 3. Topcoat UV dosage: 150g / ㎡, unit price 60 yuan / kg, required 9 yuan / ㎡.
[0047] 4. Liquid ceramic cover: 28 yuan / ㎡.
[0048] 5. Processing cost (calculated based on 40,000 large panels per month): 4,000 square meters of workshop, 12 employees, 300,000 yuan for building a small laboratory. 2 million yuan for purchasing spraying and 3D printing equipment, 600,000 yuan per year for factory rent, 800,000 yuan for raw materials, 900,000 yuan for total labor salary (per year), 100,000 yuan per year for business entertainment, inspection, research, etc.
[0049] The comprehensive production cost is 100~120 yuan / ㎡, 40,000 boards per month, 360 yuan / board, totaling 360*40,000=144.4 million yuan / month.
[0050] The average sales market price is 200 yuan / ㎡, 600 yuan per board, and 24 million yuan per month.
[0051] Sales expenses are 3 million yuan / month, gross profit is 6.6 million yuan / month, and annual gross profit is approximately 70 million yuan.
[0052] Example four.
[0053] Taking the Jiangmen ceramic faucet trial production as an example, the production workshop invested 12.8 million yuan, with an annual output of 49,500 sets. The production cost is shown in Table 5 below: Table 5 Product cost
[0054] According to comprehensive estimates, the investment is 12.82 million yuan, the annual output value is 22.27 million yuan, the cost is 10.12 million yuan, and the annual gross profit margin is 12.15 million yuan, with low input cost.
Claims
1. A method for preparing liquid ceramics, characterized in that: The following steps are involved: S1: Add 150g of silica sol, 90g of silane composite modifier and 10g of accelerator into the reactor in sequence; S2: stirring the mixed solution in step S1, so that the silica sol undergoes a polycondensation reaction to form a three-dimensional porous network structure connected by silicon-oxygen bonds, and at the same time, the silane-based composite modifier undergoes a dehydration condensation reaction with the silica sol, so that the silanol or hydroxyl groups in the silica sol react and connect to form long chains interspersed in the three-dimensional porous network structure; S3 changes the accelerator component to adjust the pH value, repeats steps S1 to S2 to conduct experiments, and determines the accelerator with the best component by observing the reaction rate in step S2 and the product after the reaction; S4 determines the quality of the dispersant through the additive test, and then determines the quality of the antifoulant through the antifoulant test; After determining 0.5 g of dispersant, 3.0 g of antifouling agent and 10 g of accelerator of the optimal component, S5 adds 10 g of accelerator of the optimal component, 90 g of silane composite modifier, 10 g of accelerator, 0.5 g of dispersant, 0.3 g of wetting agent, 3.0 g of antifouling agent and 0.1-0.3 g of isopropanol in sequence according to the weight ratio, and after sufficient reaction, it is dried to form a glaze layer.
2. The method for preparing a liquid ceramic according to claim 1, characterized in that: The silane-based composite modifier includes a composite modifier formed by mixing silane and a bridging resin-R group or a composite modifier formed by mixing a silane coupling agent and a bridging resin-R group.
3. The method for preparing a liquid ceramic according to claim 1, characterized in that: The accelerator is a mixed solution of acetic acid, citric acid and formic acid.
4. The method for preparing a liquid ceramic according to claim 1, characterized in that: The reaction formula of the polycondensation reaction of the silica sol in step S2 is as follows: 。 5. The method for preparing liquid ceramic according to claim 1, characterized in that: The step S2 also includes a resin hydrolysis reaction, after which an active functional group with R-COOH or R-OH is generated. The reaction formula for generating the R-OH active functional group is as follows: ; The active functional groups of R-COOH or R-OH undergo dehydration condensation reaction with silanol (-SiOH) or hydroxyl (-OH) in silica sol. The reaction formula is as follows: 。 6. The method for preparing liquid ceramic according to claim 1, characterized in that: The dispersant is selected through an additive test, and the test is as follows: Add different types of additives in the same volume into step S2, observe the test effects of different types of additives, screen out the three best additives in the test effects, and then conduct tests again in different proportions to obtain the additives with the best proportion in the test effects, and mix the additives with the best proportion to form a dispersant for preparing liquid ceramic raw materials.
7. The method for preparing liquid ceramic according to claim 6, characterized in that: The antifouling agent is selected through an antifouling agent test, and the test is as follows: Different types of antifouling agents are added to step S2 in the same volume, the test effects of different types of antifouling agents are observed, the best antifouling agent in the test effect is screened out, and then the test is carried out again at different proportions to obtain the best ratio range in the test effect, and further tests are carried out at different proportions in the best ratio range to screen out the antifouling agent with the best ratio, and finally the antifouling agent with the best ratio is determined as the antifouling agent for preparing liquid ceramic raw materials.
8. The method for preparing liquid ceramic according to claim 1, characterized in that: Adding color paste to liquid ceramics can form liquid ceramics of different colors.
9. The liquid ceramic prepared by the method for preparing liquid ceramic according to claim 1, characterized in that: The following raw materials are prepared according to weight ratio: 150g silica sol; 90g silane composite modifier; 10g accelerator; Dispersant 0.5 g; wetting agent 0.3 g; antifouling agent 3.0 g; isopropanol 0.1~0.3 g.
